Relationship between caregiver burden of older adults and sleep: a mixed-methods study. - Costa, Patrício de Almeida; Silva, Maria Eduarda de Barros Wanderley; Nogueira, Matheus Figueiredo; Souza, Jane Carla de (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2025)
Objective: to assess the relationship between caregiving burden and sleep health among caregivers of older adults, and to understand their perceptions of this relationship. Method: a mixed-methods study was conducted with 73 caregivers. Data collection included a sociodemographic and occupational questionnaire, Zarit Burden Interview, Sleep Diary, Pittsburgh Sleep Quality Index, and semi-structured interviews. Quantitative data were analyzed using descriptive and bivariate statistics (p<0.05), and qualitative data were processed using IRAMUTEQ software and Bardin’s content analysis. Results: 67.1% of participants presented moderate to severe caregiver burden, associated with irregular sleep schedules, shorter sleep duration, and poorer sleep quality. Additionally, 47.9% reported poor sleep quality, more prevalent among women, urban residents, and those responsible for household tasks. Narratives revealed that burden interferes directly with sleep, causing nighttime awakenings and daytime sleepiness. A support network was identified as a protective factor. Final considerations and implications for practice: caregiver burden negatively impacts sleep quality, highlighting the need for supportive public policies and underscoring the relevance of nursing in home care, particularly in the early identification and management of burden and in the promotion of caregiver well-being.